Alteration of acute toxicity of inorganic and methyl mercury to Daphnia magna by dietary addition - Christopher A. Hylton (Nature Portfolio, 2021)
Abstract Acute toxicity of inorganic mercury [Hg(II)] and methylmercury (MeHg) to Daphnia magna was characterized using a 48-h static, non-renewal acute toxicity test, in which we compared the toxicity of Hg(II) and MeHg in the absence (water-only) and presence of diet [green alga (Raphidocelis subcapitata), yeast, Cerophyll, and trout chow (YCT), or both]. Overall, Hg(II) is more toxic to D. magna than MeHg, with 48-h median lethal concentrations (LC50s) being 4.3 µg/L (95% confidence interval: 4.1–4.5 µg/L) for Hg(II) and 14.3 µg/L (13.2–15.3 µg/L) for MeHg. For Hg(II), the addition of any diet would significantly increase its 48-h LC50, but the 48-h LC50 for MeHg decreased significantly to 7.1 µg/L (6.4–7.8 µg/L) with the algal addition. We also show that the addition of diets significantly influenced the levels and speciation (dissolved vs. particulate) of both Hg forms in the test solution. The bioaccumulation of Hg(II) and MeHg was impacted by the dietary addition, and it appears that the body residue level triggering mortality varied widely among treatments. The results suggest that standard short-term toxicity tests (water-only) should be supplemented with extra tests with dietary addition to provide a more environmentally relevant estimation of short-term toxicity of chemical compounds.